Understanding How Teachers Deal with Their Emotions : Developing Indonesian Teacher Emotional Regulation Inventory (ITERI) - Amijaya, Ivan Ligan; Mangunsong, Frieda Maryam (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to develop a valid and reliable measurement tool that specifically explores the emotion regulation strategies used by teachers in Indonesia. This study used a cross-sectional survey method with a quantitative approach. The study involved 337 elementary school teachers from various regions across Indonesia, selected using convenience sampling. Data were collected through both offline printed questionnaires and online surveys via Google Forms. The validity of ITERI was assessed through cognitive interviews, Content Validity Index (CVI), and Confirmatory Factor Analysis (CFA). Cronbach's Alpha analysis was also conducted to evaluate reliability and descriptive analysis was performed. The results showed that 22 of 27 items in ITERI are valid in measuring six dimensions: situation selection, situation modification, attention deployment, cognitive reappraisal, suppression, and seeking social support. However, only five of six dimensions of the ITERI showed sufficient reliability, with the situation modification dimension being the least reliable. This study also found that teachers employ a diverse range of emotion regulation strategies. Therefore, teachers need to develop the ability to select appropriate strategies for the specific situations and emotions they encounter. ITERI could serve as a valuable tool for measuring and describing the emotional regulation abilities of Indonesian teachers in school contexts.